Endoscopic Papillotomy in Infancy Due to Biliary Cutaneous Fistula - N. ÖRMECİ and A. ABASIYANIK and M. BÜLBÜL and H. AKA and H. ATAYURT and C. YURTAYDIN and A. DÖKMECi and Ö. UZUNALİMOĞLU (Turkish Journal of Gastroenterology, 2020)
-